Monday, April 24, 2017

elementary number theory - Show aBbbZ+bBbbZ=gcd(a,b)BbbZ



I have the following problem:



Let a,bZ. Show that {ax+by : x,yZ}={ngcd(a,b) : nZ}




I understand that the Bezout's lemma says that gcd(a,b)=ax+by, so Im not really how you would go about proving the above, it doesn't really make sense to me. Any help is appreciated1


Answer



By Bezout, for some i,jZ:  ngcd(a,b)=n(aj+bk) gcd(a,b)ZaZ+bZ. Reversely,



gcd(a,b)a,bgcd(a,b)ax+by, so ax+by=ngcd(a,b), so aZ+bZgcd(a,b)Z






Or we can induct. wlog a,b>0 by aZ=aZ,(±a,±b)=(a,b), and it is true if a or b=0.




Proof by induction on size:=a+b. True if a=b: aZ+aZ=aZ. Else ab. By symmetry, wlog a>b. aZ+bZ=(ab)Z+bZ=(ab,b)Z=(a,b)Z because the green instance has smaller size=(ab)+b=a<a+b, so induction applies.   QED


No comments:

Post a Comment

analysis - Injection, making bijection

I have injection f:AB and I want to get bijection. Can I just resting codomain to f(A)? I know that every function i...